Cover Feature: Multifunctional and Sustainable Fe‐Iminopyridine Complexes for the Synthesis of Cyclic Carbonates (ChemSusChem 2/2019). Issue 2 (25th January 2019) - Seong, Eun Young; Kim, Jae Hyung; Kim, Nam Hee; Ahn, Kwang‐Hyun; Kang, Eun Joo
Abstract : The Cover Feature shows the multifunctional and sustainable Fe–iminopyridine complex for the formation of cyclic carbonates from epoxides and CO2 under mild temperature and pressure. The Lewis‐acidic Fe metal, one of the five most abundant metals in the Earth's crust, and the hydrogen bond donors in the easily modifiable iminopyridine ligands in combination with a nucleophilic halide exhibit high catalytic activity, affording a single‐component, cocatalyst‐free catalytic system. Using this approach, methods towards greener CO2 ‐recycling processes can be developed for the preparation of valuable chemicals with potential industrial applications. More information can be found in the Communication by Seong et al. onpage 409 in Issue 2, 2019 (DOI:10.1002/cssc.201802563 ).